Being baby friendly: evidence-based breastfeeding support. Issue 2 (7th October 2014) - Cleminson, J; Oddie, S; Renfrew, M J; McGuire, W
Abstract : Breast feeding improves important outcomes for mothers and infants. In the UK, breastfeeding rates have historically been low, particularly among socially disadvantaged young women. Although there have been gradual increases in breastfeeding initiation rates since 2000, rates of exclusive breast feeding and continuation until 6 months remain lower than those in similar countries. This review summarises the evidence for effective and cost-effective strategies to help women, particularly those in low income groups, make informed choices, overcome barriers and establish and maintain breast feeding. We describe the development and impact of the Unicef Baby Friendly Initiative, and the roles and responsibilities, and challenges and opportunities that clinicians have in promoting breast feeding and maintaining a baby-friendly culture and environment.